An Economic Evaluation of Food Safety Education Interventions: Estimates and Critical Data Gaps - Zan, Hua; Lambea, Maria; McDowell, Joyce; Scharff, Robert L. (Journal of Food Protection, 2017)
The economic evaluation of food safety interventions is an important tool that practitioners and policy makers use to assess the efficacy of their efforts. These evaluations are built on models that are dependent on accurate estimation of numerous input variables. In many cases, however, there is no data available to determine input values and expert opinion is used to generate estimates. This study uses a benefit-cost analysis of the food safety component of the adult Expanded Food and Nutrition Education Program (EFNEP) in Ohio as a vehicle for demonstrating how results based on variable values that are not objectively determined may be sensitive to alternative assumptions. In particular, the focus here is on how reported behavioral change is translated into economic benefits. Current gaps in the literature make it impossible to know with certainty how many people are protected by the education (what are the spillover effects?), the length of time education remains effective, and the level of risk reduction from change in behavior. Based on EFNEP survey data, food safety education led 37.4% of participants to improve their food safety behaviors. Under reasonable default assumptions, benefits from this improvement significantly outweigh costs, yielding a benefit-cost ratio of between 6.2 and 10.0. Incorporation of a sensitivity analysis using alternative estimates yields a greater range of estimates (0.2 to 56.3), which highlights the importance of future research aimed at filling these research gaps. Nevertheless, most reasonable assumptions lead to estimates of benefits that justify their costs.